Die Masken aus der Nekropole von Lipari - Tommaso Ismaelli (Les Carnets de l’ACoSt)
The book, a reworking of the author’s Habilitationsschrift discussed at the Freie Universität of Berlin, tackles the complex phenomenon of votive offerings in the form of terracotta masks from the Classical and Hellenistic necropolis of Lipari. This important category of archaeological material has been the object of various well-known studies, most notably by L. Bernabò Brea and M. Cavalier. It is one of the most important classes of coroplastic art from Magna Graecia and Sicily because of not only its quality and variety but also its fundamental contribution to our knowledge of local ritual practices, funerary customs, and religious beliefs in the 4th and 3rd centuries BCE.